Massive Online Obsessive Compulsion: What are They Saying Out There about the Latest Phenomenon in Higher Education? - Dolan, Vera L B (International Review of Research in Open and Distributed Learning, 2014)
This article is a review of ideas, comments, and inquiries about massive open online courses (MOOCs) gathered from a wide variety of online journal and magazine articles, and web blogs. As a seasoned “traditional” online educator, as well as a student participant in several MOOCs, I also take the opportunity to share my personal insight from my own learning experiences, with the goal of illustrating some of the concerns unearthed in my research. One serious issue regarding MOOCs is that some learners can feel isolated and/or neglected, particularly when they perceive that other course participants and/or the professor are ignoring their contributions. Our era has witnessed “the McDonaldization of Education” (Lane & Kinser, 2012), in which one size fits all and information is delivered to student “customers” via systematically managed “factories” whose overseers frown upon any supposed waste of valuable resources or human effort. In the mass-appeal environment of a MOOC, it is quite possible that a student will receive no customized feedback from nominal experts in the field. Lack of meaningful interaction is likely a key factor driving high attrition numbers in the online education environment – numbers that are apparently even higher in the case of MOOCs.